An overlapping grid spectral collocation analysis on a newly developed hybrid nanofluid flow model - Amir Yaseen Khan; Musawenkhosi Patson Mkhatshwa; Sabyasachi Mondal; Melusi Khumalo; Noor Fadiya Mohd Noor (Propulsion and Power Research, 2024)
The present study investigates the axisymmetric stagnation point radiative flow of a Cu-Al2O3/water hybrid nanofluid over a radially stretched/shrunk disk. In this paper, a new mathematical model has been developed by taking into consideration the concept of different nanoparticles concentration in a hybrid nanofluid, which are Brownian motion and thermophoresis of nanoparticles. A new model for entropy generation has also been provided in the present study. The non-dimensional governing equations of the developed mathematical model are solved using newly developed and efficient overlapping grid spectral collocation method. Numerical stability and residual error test are provided here to show the accuracy of the numerical method in this mathematical model. The outcomes of fluid flow, temperature, and two different types of concentration profiles are depicted, and described in graphical and tabular forms. For the limiting instances, comparison shows excellent agreement among current and results established in the literature. Increasing the strength of magnetic field is seen to increase the radial component of fluid velocity as well as the entropy generated within the system. Two different nanofluid concentration profiles are increasing and decreasing with rising thermophoresis and Brownian motion parameters, respectively, from a particular height above the disk because of the revised nanofluid boundary condition. Temperature profile increases here with increasing Biot number, and increasing Brinkman number causes higher entropy generation number for both stretching and shrinking disks. The enhanced thermal characteristics of the hybrid nanofluid over the single particle nanofluid has been observed.